The tombs - Cussler, Clive; Perry, Thomas, 1947- (New York : G.P. Putnams Sons, 2012)
Husband-and-wife team Sam and Remi Fargo are intrigued when an archaeologist friend requests their help excavating a top secret historical site. What they find will set them on a hunt for a prize greater than they could ever imagine. The clues point to the hidden tomb of Attila the Hun, the High King who was reportedly buried with a vast fortune of gold and jewels and plunder . . . a bounty that has never been found. As they follow the trail through Hungary, Italy, France, Russia, and Kazakhstan--a trail that they discover leads them not to one tomb, but five--the Fargos will find themselves pitted against a thieving group of amateur treasure hunters, a cunning Russian businessman, and a ruthless Hungarian who claims direct descent from Attila himself . . . and will stop at nothing to claim the tombs' riches as his own.
Keywords: Archaeologists -- Fiction; Tombs -- Fiction; Treasure troves -- Fiction